MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MEWARNAI - Suharti; Kholis, Nur (LPPM STAI DARUSSALAM LAMPUNG, 2020)
This study aims to improve fine motor skills through coloring activities. Fine motor skills are very important to support the next level of education. This type of research is a classroom action research conducted in 2 cycles. The subjects of this study were 16 children of group B RA Babussalam, Bauh Gunung Sari Village, with the object of fine motor skills. The data collection techniques used were observation and documentation. Data analysis used descriptive qualitative and quantitative. The results showed that the fine motor skills before the action had an average percentage of 64.58% with BSH criteria, an increase of 3.65% in the first cycle was in the BSH criteria, in the second cycle it had an increase of 11.72% and became BSB. . Based on these data, it can be concluded that the child's fine motor skills have increased and achieved success indicators of more than 75% with the criteria of Very Good Development. The positive contribution of this research is to provide information to the wider community that playing coloring activities can help improve fine motor skills in early childhood.